Effects of Increasing Soybean Meal Levels on Growth Performance and Carcass Characteristics of Pigs in Grower and Late-Finishing Phases - Jamil E. G. Faccin; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2023)
Four experiments were conducted to determine the effects of increasing soybean meal (SBM) on grower and late-finishing pig performance. In Exp. 1, a total of 615 pigs (initially 95.2 ± 1.51 lb) were used in a 28-d trial with 14 replicate pens per treatment and 8 to 10 pigs per pen. Pens of pigs were randomly assigned to 1 of 5 dietary treatments which were corn-based with soybean meal levels of 19.1, 22.6, 26.3, 29.9, or 33.5%. In Exp. 2, a total of 615 pigs (initially 225.5 ± 3.42 lb) were used in a 30-d trial with 14 replicate pens per treatment and 8 to 10 pigs per pen. Pens of pigs were randomly assigned to 1 of 5 dietary treatments which were corn-based with soybean meal levels of 11.2, 14.2, 17.2, 20.2, or 23.2%. In both experiments, treatments were assigned in a completely randomized design and soybean meal inclusion was increased, replacing feed grade amino acids to form the treatments. For Exp. 1, increasing SBM increased (linear,P= 0.038) ADG and improved (P<0.001) feed efficiency, with the greatest change from increasing SBM from 19.1 to 22.6%. For late-finishing pigs (Exp. 2), no differences (P>0.10) were observed for any growth performance or carcass criteria. Experiments conducted in a second series were conducted with the same basic procedures as Exp. 1 and 2, but all diets contained DDGS, and were conducted in a commercial facility. In Exp. 3, a total of 1,080 pigs (initially 86.1 ± 1.72 lb) were used in a 28-d trial with 10 replicate pens per treatment and 27 pigs per pen. Pens of pigs were assigned to 1 of 4 dietary treatments which were corn-20% DDGS-based and soybean meal was added at 18.2, 23.5, 28.9, or 34.3%. For Exp. 4, a total of 1,080 pigs (initially 225.2 ± 2.50 lb) were used in a 33-d trial with 10 replicate pens per treatment and 27 pigs per pen. Pens of pigs were assigned to 1 of 4 dietary treatments which were corn-10% DDGS-based with soybean meal levels of 9.5, 13.5, 17.5, or 21.5%. When DDGS was included in the diet, no differences (P>0.10) were observed for any growth performance criteria for early- or late-finishing pigs. In conclusion, increasing levels of SBM (up to 33.5% of the diet) in grower pig diets linearly improved ADG and feed efficiency in corn-soybean meal-based diets. However, when DDGS was included in the diet, pig performance was not affected when SBM ranged from 18.2 to 34.3%. For late-finishing pig diets, increasing the SBM from approximately 10 to 23% in diets with or without DDGS did not result in any changes in growth and carcass parameters. These results suggest that high levels of SBM in the diet (no feed-grade amino acids) are well tolerated and do not negatively affect pig growth.
Keywords: carcass yield; crude protein; finishing pig; soybean meal